Vilken rektor önskas? En kvalitativ studie av den statliga rektorsutbildningen - Alkeberg,Johanna (2019)
The aim of this study was to examine the governance of the education for principals, and what type of manager for Swedish schools the content of the education represents. The different manager types is influenced by Lennart Lundquists theory of five managers for the public sector. In addition to the discourse analysis of the content in the education for principals, through its target document. I also examined the problematization that was underlying the new education for principles, with Carol Bacchis method for analyzing policy: What’s the problem represented to be? The result shows that the education for principles first and foremost are influenced by the manager type “direktören”. This type of manager is an expert in management and leadership strategy and is a manager in the public sector that is strongly influenced by the private sector. The problematization which underlies the education for principals are: solving various problems with better leadership, to distance principals profession from teachers and to make the profession as a principal more attractive, by enable more opportunities for a further career in management
Keywords: Rektorsprogrammet; förvaltningschef; styrning; ledning; Bacchi; rektor